Reorganization of continent-scale sediment routing based on detrital zircon and rutile multi-proxy analysis - Dröllner, Maximilian; Barham, Milo; Kirkland, Chris (WILEY, 2023)
The duration and extent of sediment routing systems are intrinsically linked to crustal- to mantle-scale processes. Therefore, distinct changes in the geodynamic regime may be captured in the detrital record. This study attempts to reconstruct the sediment routing system of the Canning Basin (Western Australia) during the Early Cretaceous to decipher its depositional response to Mesozoic-Cenozoic supercontinent dispersal. Specifically, we reconstruct source-to-sink relationships for the Broome Sandstone (Dampier Peninsula) and proximal modern sediments through multi-proxy analysis of detrital zircon (U–Pb, Lu–Hf and trace elements) and detrital rutile (U–Pb and trace elements). Multi-proxy comparison of detrital signatures and potential sources reveals that the majority of the detrital zircon and rutile grains are ultimately sourced from crystalline basement in central Australia (Musgrave Province and Arunta region) and that proximal sediment supply (i.e., Kimberley region) is negligible. However, a significant proportion of detritus might be derived from intermediate sedimentary sources in central Australia (e.g., Amadeus Basin) rather than directly from erosion of crystalline basement. Broome Sandstone data are consistent with a large-scale drainage system with headwaters in central Australia. Contextualization with other broadly coeval drainage systems suggests that central Australia acted as a major drainage divide during the Early Cretaceous. Importantly, reorganization after supercontinent dispersal is characterized by the continuation of a sediment pathway remnant of an earlier transcontinental routing system originating in Antarctica that provided a template for Early Cretaceous drainage. Review of older Canning Basin strata implies a prolonged denudation history of central Australian lithologies. These observations are consistent with the long-lived intracontinental tectonic activity of central Australia governing punctuated sediment generation and dispersion more broadly across Australia and emphasize the impact of deep Earth processes on sediment routing systems.